ANALYSIS OF THE EFFECTIVENESS OF CHARACTER EDUCATION PROGRAMS IN IMPROVING STUDENTS' ATTITUDES OF DISCIPLINE AND RESPONSIBILITY - Seno Lamsir (International Journal of Teaching and Learning, 2026)
This research aims to analyze the effectiveness of character education programs in improving students' attitudes of discipline and responsibility through a review of various related literature. The research method used is a literature review, by collecting and analyzing data from various previous studies related to the implementation of character education programs in schools. The results of the study show that the character education program has a significant positive effect on the formation of students' attitudes of discipline and responsibility. Students involved in this program tend to show an increase in compliance with school regulations, punctuality in submitting assignments, and concern for their duties and responsibilities. This research concludes that the character education program is effective as a strategic tool for forming disciplined and responsible behavior, which ultimately contributes to the formation of a generation with strong character and high morals. Recommendations for further research are to focus on developing practical learning methods and more interactive guidance to further maximize the results of character education programs.